ANTIOXIDANT ACTIVITY OF NON-PSYCHOACTIVE CANNABIS VARIETIES FROM NORTH CAUCA, COLOMBIA - Arango Romero, Paola Andrea; Delgado, Jhan Carlos; Muñoz, Sandra Marcela; Llanos, Luis; Benítez, Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The present study aim to publicize the chemical composition and possible medicinal potential of varieties of non-psychoactive cannabis grown in the department of Cauca. Cannabinoids were identified and quantified by high-performance liquid chromatography coupled to an ultraviolet detector (HPLC/UV) for the analysis of the flower, and gas chromatography coupled to a mass spectrometer (GC-MS) for the analysis of the ethanolic extracts and content terpenes. Phenols were quantified by reaction with the Folin & Ciocalteau reagent; for the determination of flavonoids and anthraquinones, the extracts were treated with AlCl3. Finally, to determine the antioxidant activity, three methods were used: DPPH, ABTS and FRAP. It was possible to determine that varieties A and B contained percentages of total tetrahydrocannabinol (THC) less than 1% and percentages of total cannabidiol (CBD) between 9-15%. In the ethanolic extracts concentrations (m/m) of CBD were reached in varieties A and B, of 10% and 13.7%, respectively. Nine terpenes from sample A and seven from sample B were identified and quantified, with β-caryophyllene being the most abundant in both. Considering that there is evidence in the literature that the CBD/THC ratio influences biological activity, ethanolic extracts of varieties A and B are expected to have moderate to low antioxidant activity, which, according to some researchers, it may be associated with the neuroprotective effect, which may be favored by the presence of β-caryophyllene.